Modulation of the effective density and refractive index of carbon nanotube forests via nanoimprint lithography. (April 2018) - Park, Sei Jin; Ok, Jong G.; Park, Hui Joon; Lee, Kyu-Tae; Lee, Jae Hyuk; Kim, Jeong Dae; Cho, Eikhyun; Baac, Hyoung Won; Kang, Shinill; Guo, L. Jay; Hart, A. John
Abstract: The unique properties of carbon nanotubes (CNTs) allow them to be used in various optical applications, such as ultra-dark surfaces, bolometers, metamaterial cloaks, and anisotropic absorbers. In particular, organization of CNTs with controlled density at the sub-micrometer scale could enable new strategies to engineer optically active surfaces. Here, we present a new strategy to engineer the density-dependent optical properties of CNT forests by patterning of catalyst film via nanoimprint lithography (NIL) followed by atmospheric pressure chemical vapor deposition (CVD) synthesis of CNTs. Via this approach, we demonstrate atmospheric pressure growth of CNT structures with widths of 80–350 nm. These structures form self-supporting arrays with height exceeding 500 μm, representing aspect ratios well over 1000:1. Optical attenuation measurement places the density of NIL patterned forests to be a fraction of the density of unpatterned CNT forests, confirming that the CNT density is effectively controlled by the catalyst coverage. The infrared absorbance measurements corroborate the density control, and Kramers-Kronig analysis shows that the refractive indices of the NIL patterned CNT forests are tunable in the range of 1–1.8. Graphical abstract: Image 1